Electrode for secondary battery, method for producing same, and secondary battery including said electrode

JP7631543B2Active Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023546327
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-30
Filing Date
2022-07-18
Publication Date
2025-02-18
Estimated Expiration
2042-07-18

AI Technical Summary

Benefits of technology

【0018】 本発明の二次電池用電極は、粒子サイズが小さい活物質を含みながらも優れる柔軟性を持ち、壊れることが最小化された乾式電極フィルムを含むことで優れる品質を提供する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631543000003
    Figure 0007631543000003
  • Figure 0007631543000004
    Figure 0007631543000004
  • Figure 0007631543000005
    Figure 0007631543000005
Patent Text Reader

Abstract

The present invention provides an electrode for a secondary battery, the electrode comprising: a dry electrode film including an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillated binder; and a current collector on which the electrode film is laminated; a method for producing the electrode; and a secondary battery including the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0100746 filed on July 30, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to an electrode for a secondary battery, a method for producing the same, and a secondary battery comprising said electrode. [Background technology]

[0003] Recently, interest in energy storage technology has been increasing. As the range of applications expands to include mobile phones, camcorders, laptops, and even the energy of electric vehicles, efforts in the research and development of electrochemical devices are gradually being made.

[0004] In this regard, electrochemical devices are the field that has been receiving the most attention, and among them, the development of rechargeable secondary batteries has been the focus of attention. Recently, in the development of secondary batteries, research and development into new electrode and battery designs has been actively conducted in order to improve capacity density and specific energy.

[0005] Among secondary batteries currently in practical use, lithium secondary batteries are in the spotlight due to their advantages of having a higher operating voltage and a much higher energy density than conventional batteries.

[0006] Meanwhile, with the expansion and development of applications of secondary batteries, there is a continuous demand for improvements in electrodes, such as lower resistance, higher capacity, mechanical properties, and improved productivity.

[0007] Electrodes for secondary batteries are generally manufactured by laminating an electrode active material layer formed by binding an active material and an optional conductive material with a binder on a current collector. Specifically, a method is generally used in which a slurry containing an electrode active material, a binder, a conductive material, etc. is applied onto a current collector, and the solvent is removed by heating or the like. However, this method has a drawback in that the solvent must be removed from the electrode slurry, which reduces the economy and productivity.

[0008] Therefore, in order to overcome these shortcomings, a method for manufacturing an electrode without using an electrode slurry has been proposed. That is, a technique for manufacturing an electrode film by mixing an active material, a binder, and a conductive material without a liquid medium such as a solvent or a dispersion medium, and then passing the powder mixture through a rolling roll is being actively developed. Generally, in this method, a binder called a "fibrillizable binder" or a "fibril-forming binder" is used. The binder binds the active material and the conductive material while being fibrillated, thereby enabling the manufacture of a free-standing electrode film. The electrode film manufactured in this way is used for manufacturing an electrode by laminating it on a current collector.

[0009] The above-mentioned conventional method offers various advantages over the method of applying an electrode slurry, but has the disadvantage that when the active material particle size is small, the mixture becomes very hard, making subsequent processing difficult, and it is easily broken due to lack of flexibility.

[0010] Therefore, there is a need to solve such problems. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Korean Patent Publication No. 10-2006-0025230 Summary of the Invention [Problem to be solved by the invention]

[0012] The present invention has been devised to solve the above-mentioned problems of the prior art, and aims to provide an electrode for a secondary battery including a dry electrode film that contains an active material having a small particle size, yet has excellent flexibility and is minimally broken.

[0013] Another object of the present invention is to provide a method for producing an electrode for a secondary battery, which can efficiently produce the electrode.

[0014] Another object of the present invention is to provide a secondary battery having excellent driving characteristics and life characteristics by including the electrode. [Means for solving the problem]

[0015] In order to achieve the above object, the present invention provides The present invention provides an electrode for a secondary battery, comprising: a dry electrode film including an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillated binder; and a current collector on which the electrode film is laminated.

[0016] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: (a) mixing an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillizable binder; (b) performing shear mixing on the mixture to fiberize the fibrillizable binder to produce a dry electrode mix; (c) pulverizing the dry electrode mix to produce a powder; (d) compressing the powder into a free-standing film form; and (e) laminating the free-standing film on a current collector.

[0017] The present invention also provides a secondary battery including the electrode. Effect of the Invention

[0018] The electrode for a secondary battery according to the present invention provides excellent quality by including a dry electrode film that has excellent flexibility and is minimally broken while including an active material having a small particle size.

[0019] In addition, the method of manufacturing a secondary battery electrode of the present invention provides the effect of greatly improving the manufacturing efficiency of the electrode.

[0020] In addition, the secondary battery of the present invention includes the electrode, and thus provides excellent driving characteristics and life characteristics. [Brief description of the drawings]

[0021] [Figure 1] 1 is a photographed image showing the morphology of a fibrillated binder contained in an electrode according to one embodiment of the present invention. [Diagram 2] 1 is a diagram showing a schematic structure of a free-standing film produced from active material particles. [Diagram 3] FIG. 2 is a schematic diagram showing the production form of a free-standing film when one type of fibrillizable binder is used as one embodiment of the present invention. [Figure 4] FIG. 2 is a schematic diagram showing a method for producing a free-standing film when two or more fibrillizable binders having different glass transition temperatures are used as one embodiment of the present invention. [Diagram 5] Photograph showing the morphology of a free-standing film produced in Example 1 as one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings in order to enable those skilled in the art to easily practice the present invention. However, the present invention may be embodied in several different forms and is not limited to the embodiments set forth herein.

[0023] When referring to a component as being "stacked or disposed on top of or underneath another component," it should be understood that the component may be stacked or disposed directly on the other component, but there may also be other components in between.

[0024] The electrode for a secondary battery of the present invention is characterized by comprising: a dry electrode film including an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillated binder; and a current collector on which the electrode film is laminated.

[0025] As the particle size of the active material contained in the electrode becomes smaller, the degree of integration of the active material in the electrode increases, and the load amount of the active material per unit volume increases, which is advantageous in terms of battery capacity by increasing the energy density. Therefore, there is a need to use an active material with a small particle size in the manufacture of electrodes.

[0026] However, when an active material having an average particle size of 3 μm or less is used to manufacture a dry electrode film, the electrode manufacturing knead becomes very hard and difficult to process into a film shape, and even if manufacturing is possible by applying high pressure, the manufactured electrode film is not flexible enough and easily breaks. Therefore, it is almost impossible to manufacture a dry electrode film using an active material having an average particle size of less than 3 μm using conventional technology. In addition, active materials having an average particle size of less than 0.05 μm are difficult to handle and expensive to use, making them difficult to apply to the present invention.

[0027] The fundamental reason why it is difficult to use small-sized active materials is believed to be that when high shear mixing is performed, the bonding characteristics between particles increase, so the kneaded mixture becomes easily hardened, and the internal pores decrease, reducing the space available for shape deformation, as shown in Figure 2. In addition, as the size of the active materials decreases, the contact area between the active materials increases, so the kneaded mixture becomes easily hardened, and the pressure required to form the film becomes greater than the equipment limit.

[0028] The present invention has been developed for the first time to overcome the manufacturing difficulties described above. The electrode produced by the present invention provides the effect of improving the driving characteristics and life characteristics of a battery.

[0029] In the present invention, the average particle size of the active material is set based on D50.

[0030] The secondary battery electrode of the present invention is a positive electrode or a negative electrode.

[0031] In one embodiment of the invention, the fibrillated binder may include polytetrafluoroethylene.

[0032] In one embodiment of the present invention, the fibrillated binder may further include acrylic modified polytetrafluoroethylene. The acrylic modified polytetrafluoroethylene refers to a binder in which an acrylic polymer is mixed with polytetrafluoroethylene to modify the properties of polytetrafluoroethylene. The acrylic modified polytetrafluoroethylene can improve the strength and flexibility of the freestanding film because the acrylic binder provides excellent adhesion above the glass transition temperature. The polytetrafluoroethylene and the acrylic polymer may be mixed in a weight ratio of 7:3 to 3:7, and preferably in a weight ratio of 6:4 to 4:6.

[0033] The polytetrafluoroethylene contained in the acrylic modified polytetrafluoroethylene is a polymer that can be fibrillated, and may have a high molecular weight, for example, a melt viscosity of 108 poise or more at 380° C. In addition, when expressed in terms of standard specific gravity (ASTM D-1457), the standard specific gravity may be 2.210 or less, preferably 2.200 to 2.130.

[0034] Examples of the acrylic polymer include hydrocarbon monomers that are liquid at room temperature, such as α,β-ethylenically unsaturated carboxylic acid esters, such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, lauryl acrylate, and stearyl acrylate; hydroxyalkyl esters of α,β-ethylenically unsaturated carboxylic acids, such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, and 3-hydroxypropyl methacrylate; alkoxyalkyl esters of α,β-ethylenically unsaturated carboxylic acids, such as diethylene glycol methacrylate; α,β-ethylenically unsaturated carboxylic amides, such as acrylamide and methylol methacrylamide; α,β-ethylenically unsaturated carboxylic acids, such as acrylic acid, methacrylic acid, itaconic acid, maleic anhydride, maleic acid, fumaric acid, and crotonic acid; and acrylonitrile. At least one of these may be used.

[0035] The acrylic modified polytetrafluoroethylene may be in the form of a powder, specifically, Metablen A-3000 manufactured by Mitsubishi Rayon Co., Ltd. The powder may have a structure in which polytetrafluoroethylene and an acrylic polymer are mixed together to form a matrix, or the acrylic polymer is coated on polytetrafluoroethylene.

[0036] The acrylic modified polytetrafluoroethylene may have a glass transition temperature of more than 60°C.

[0037] In one embodiment of the present invention, the fibrillated binder may contain polytetrafluoroethylene and the acrylic modified polytetrafluoroethylene in a weight ratio of 1:9 to 9:1, preferably 3:7 to 7:3.

[0038] In one embodiment of the present invention, the active material has an average particle size of 0.05 μm to 2 μm, and may have an average particle size of 0.05 μm to 1.5 μm.

[0039] In one embodiment of the present invention, the dry electrode film may include fibers fibrillated in multiple directions by preparing a dry electrode mix by first fibrillating a fibrillizable binder, pulverizing the dry electrode mix to produce a powder, and compressing the powder to form a dry electrode film by second fibrillating the fibrillizable binder.

[0040] The method for manufacturing an electrode for a secondary battery according to the present invention is characterized by including the following steps.

[0041] (a) mixing an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillizable binder; (b) performing shear mixing on the mixture to fiberize the fibrillizable binder to produce a dry electrode mix; (c) pulverizing the dry electrode mix to produce a powder; (d) compressing the powder into a free-standing film form; and (e) laminating the free-standing film onto a current collector. The above-described contents regarding the electrodes may all be applied to the manufacturing method, and therefore, the description of overlapping contents will be omitted.

[0042] In the step (c) of producing the powder, the powder has a particle size of 100 μm to 1000 μm, more preferably 300 μm to 1000 μm. It is not preferable to produce the powder with a particle size of less than 100 μm because it is difficult to process and the effect is limited, and it is not preferable to produce the powder with a particle size of more than 1000 μm because it is difficult to achieve a uniform thickness and rolling density when producing the powder in the form of a film.

[0043] In the present invention, a fibrillizable binder means a binder that can be made into fibers by the application of a shear force.

[0044] In one embodiment of the invention, the fibrillizable binder may comprise polytetrafluoroethylene.

[0045] In one embodiment of the present invention, the fibrillizable binder may further comprise an acrylic modified polytetrafluoroethylene.

[0046] The acrylic modified polytetrafluoroethylene may have a glass transition temperature of more than 60°C. If the glass transition temperature is lower than this temperature, the acrylic modified polytetrafluoroethylene is fiberized in the kneading step (b) and then the dry electrode knead is pulverized to a powder state in the powder production step (c), so there is no point in adding the acrylic modified polytetrafluoroethylene. That is, in one embodiment of the present invention, as shown in FIG. 4, it is preferable that the acrylic modified polytetrafluoroethylene is not fiberized in the kneading step (b) but is fiberized in the film forming step (d) due to the glass transition temperature. Due to this mechanism, the dry electrode film manufactured according to the present invention can be manufactured with high strength in both the machine direction (MD) and the transverse direction (TD). Furthermore, the dry electrode film manufactured according to the present invention can have a form in which the fibrillizable binder is fiberized in multiple directions.

[0047] In one embodiment of the present invention, the kneading step (b) may be performed at the glass transition temperature of polytetrafluoroethylene or a temperature higher than the glass transition temperature, specifically, in the range of 30 to 60° C. At this time, the upper limit of the temperature is preferably lower than the glass transition temperature of the acrylic modified polytetrafluoroethylene.

[0048] In addition, the film forming step (d) may be performed at a temperature equal to or higher than the glass transition temperature of the acrylic modified polytetrafluoroethylene, specifically, in the range of 60°C to 120°C.

[0049] In one embodiment of the present invention, the fibrillizable binder may contain polytetrafluoroethylene and the acrylic modified polytetrafluoroethylene in a weight ratio of 1:9 to 9:1, preferably 3:7 to 7:3. When contained within the above range, the manufactured dry electrode film may have high strength in both the machine direction (MD) and the transverse direction (TD), and further, may be fiberized in multiple directions to have high strength in all directions, which is preferable.

[0050] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A secondary battery including the electrode of the present invention is provided.

[0051] The secondary battery is a lithium secondary battery.

[0052] The above-mentioned invention will now be described in more detail.

[0053] <Active material> The active material may be any of the components commonly used in positive and negative electrodes. For example, when the active material is a positive electrode active material, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, and LiNi 1-x-y-z Co x M1 y M2 zAny one of the active material particles composed of O2 (where M1 and M2 are each independently selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg, and Mo, and x, y, and z are each independently 0 ≦ x < 0.5, 0 ≦ y < 0.5, 0 ≦ z < 0.5, and 0 < x + y + z ≦ 1 as atomic fractions of oxide composition elements) or a mixture of two or more of these can be included.

[0054] When the electrode active material is a negative electrode active material, it is a carbonaceous material such as natural graphite or artificial graphite (mesocarbon microbeads (MCMB), pyrolytic carbon, mesophase pitch based carbon fiber, mesophase pitches, petroleum or coal tar pitch derived cokes, etc.); lithium-containing titanium composite oxides (LTO), metals such as Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, or Fe (Me); alloys composed of the metals (Me); oxides of the metals (MeOx, e.g., SIO); and any one of the active materials selected from the group consisting of composites of the metals (Me) and carbon or a mixture of two or more of these.

[0055] The active material can be contained, for example, in an amount of 85 to 98% by weight based on the total weight of the electrode film.

[0056] <Conductive material> In one embodiment of the present invention, the conductive material is not particularly limited as long as it has conductivity without causing a chemical change in the secondary battery. For example, one or more selected from carbon blacks such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; metal powders such as aluminum, nickel powder; conductive whiskers such as zinc oxide, potassium titanate; conductive metal oxides such as titanium oxide; polyphenylene derivatives, etc. can be used.

[0057] The conductive material may be included in an amount of, for example, 1 to 10 wt %, specifically, 2 to 4 wt %, based on the total weight of the electrode film.

[0058] <Binder> The present invention may further include another binder in addition to the fibrillated or fibrillizable binder. The other binder is a component that aids in binding the active material and conductive material and adhering to the current collector, and may be any material that can be used in an electrode. Specifically, the binder may be a non-acrylic polymer or an acrylic polymer.

[0059] The acrylic polymer may be any polymer containing at least one repeating unit derived from an acrylic monomer, without any limitations. The acrylic monomer may be alkyl acrylate, alkyl methacrylate, isoalkyl (meth)acrylate, etc., where "alkyl" is an alkyl group having 1 to 10 carbon atoms, more specifically, an alkyl group having 1 to 5 carbon atoms.

[0060] Specific examples of the acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and pentyl (meth)acrylate.

[0061] The acrylic polymer is a homopolymer consisting of one type of repeating unit derived from an acrylic monomer, or a copolymer containing repeating units derived from two or more types of acrylic monomers, or a mixture of two or more of these.

[0062] Also, the acrylic polymer is a copolymer of one or more non-acrylic monomers and an acrylate monomer, such as one or more selected from the group consisting of acrylate-styrene-butadiene rubber, acrylate-acrylonitrile-styrene-butadiene rubber, methyl acrylate-styrene-butadiene rubber, methyl acrylate-acrylonitrile-styrene-butadiene rubber, ethyl acrylate-styrene-butadiene rubber, ethyl acrylate-acrylonitrile-styrene-butadiene rubber, propyl acrylate-styrene-butadiene rubber, propyl acrylate-acrylonitrile-styrene-butadiene rubber, butyl acrylate-styrene-butadiene rubber, and butyl acrylate-acrylonitrile-styrene-butadiene rubber, etc. In the case of a copolymer of a non-acrylic monomer and an acrylate monomer, the weight percent of the repeating unit derived from the acrylate monomer is 5 to 45 weight percent, specifically 5 to 35 weight percent.

[0063] The acrylic polymer may also be a mixture of two or more homoacrylic polymers, a mixture of two or more acrylic copolymers, a mixture of two or more copolymers of a non-acrylic monomer and an acrylate monomer, or a mixture of two or more of homoacrylic polymers, acrylic copolymers, and copolymers of a non-acrylic monomer and an acrylate monomer.

[0064] The non-acrylic polymer means a polymer containing one or more repeating units derived from a monomer other than an acrylic monomer, specifically, a homopolymer containing one type of repeating unit, a copolymer containing two or more different types of repeating units, a mixture of two or more different types of homopolymers, or a mixture of two or more of these.

[0065] Specific examples of the non-acrylic polymer include styrene-butadiene rubber (SBR), a mixture of polystyrene and polybutadiene, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-cotrichloroethylene, polytetrafluoroethylene (PTFE), polyvinylpyrrolidone, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. One or a mixture of two or more of the following may be used: polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), etc. Among these, polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), etc. may be preferably used.

[0066] In one embodiment of the present invention, the total binder content including the fibrillated binder is 0.1 to 10 wt %, specifically 1 to 4 wt %, based on the total weight of the electrode film. When the binder content satisfies this range, the adhesive strength between the electrode active material layer and the current collector is improved, and the improved adhesive strength can reduce the electrode resistance and prevent electrode detachment even after cell degradation, and the migration of binder to the electrode surface can be suppressed to improve ionic conductivity and electrical conductivity within the electrode.

[0067] <Current collector> The current collector may be any known current collector used in secondary batteries, without any limitation, such as stainless steel, aluminum, nickel, titanium, calcined carbon, copper, stainless steel surface-treated with carbon, nickel, titanium, or silver, aluminum-cadmium alloy, non-conductive polymer surface-treated with conductive material, non-conductive polymer surface-treated with metal, and conductive polymer.

[0068] <Electrode manufacturing> The method for producing an electrode for a secondary battery according to the present invention will be described below with reference to an example.

[0069] A method for manufacturing an electrode for a secondary battery according to an embodiment of the present invention may include the following steps.

[0070] (a) mixing an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillizable binder; (b) performing shear mixing on the mixture to fiberize the fibrillizable binder to produce a dry electrode mix; (c) pulverizing the dry electrode mix to produce a powder; (d) compressing the powder into a free-standing film form; and (e) laminating the free standing film onto a current collector.

[0071] The mixing in step (a) means mixing without a solvent. The dry mixing can be performed using a stirrer at room temperature or lower at 600 rpm to 20,000 rpm, more specifically at 1,000 rpm to 12,000 rpm, for 0.5 to 10 minutes.

[0072] The shear mixing in step (b) may include applying high shear force by shearing the mixture. Specifically, when using a device for applying shear force, such as PBV-0.1L (Irie Shokai), the mixture may be sheared at 10 rpm to 100 rpm for 1 minute to 10 minutes to apply high shear force. However, the method is not limited to this.

[0073] The high shear force is between 50N and 1000N, specifically between 100N and 500N, and more specifically between 100N and 300N.

[0074] In step (c), the powder has a particle size of 100 μm to 1000 μm.

[0075] In the step (d) of forming a free-standing film, the pressing can be performed using a Two roll mill MR-3 (Inoue Co., Ltd.) or the like.

[0076] The step (e) of laminating the free-standing film on a current collector may include a step of placing the free-standing film on a current collector and rolling the film, and the rolling may be performed using a roll press method.

[0077] <Secondary battery manufacturing> The present invention also relates to a secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, at least one of the positive electrode and the negative electrode being the above-mentioned electrode. When the electrode according to the present invention is used for only one of the positive electrode and the negative electrode, the other electrode may be any electrode known in the art without any limitation.

[0078] The secondary battery will be described below by way of example, specifically, by way of example of a lithium secondary battery.

[0079] The separator may be a porous polymer film that is generally used as a separator in a lithium secondary battery, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or may be used alone or in a laminated state. Also, an insulating thin film having high ion permeability and mechanical strength may be used. The separator may include a safety reinforced separator (SRS) having an organic / inorganic composite porous coating layer that is thinly coated on the surface of a separator substrate such as a porous polymer film, in which inorganic particles are connected and fixed via a binder polymer. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used, and the above-mentioned organic / inorganic composite porous coating layer may be applied to the porous nonwoven fabric, but is not limited thereto.

[0080] The lithium secondary battery of the present invention may be manufactured by housing the positive and negative electrode assembly in a battery case and injecting an electrolyte therein.

[0081] The electrolyte may include a lithium salt and an organic solvent for dissolving the lithium salt. The lithium salt may be any one that is commonly used in electrolytes for secondary batteries. For example, the anion of the lithium salt may be F- , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One selected from the group consisting of:

[0082] The organic solvent contained in the electrolyte may be any organic solvent used in this field without limitation. Representatively, at least one selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, gamma-butyrolactone, propylene sulfite, and tetrahydrofuran may be used.

[0083] In particular, among the carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate are preferably used since they are high-viscosity organic solvents with high dielectric constants and dissociate lithium salts in the electrolyte well. If such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, and therefore, such a mixture can be more preferably used.

[0084] Optionally, the electrolyte stored according to the present invention may further contain additives such as overcharge inhibitors that are typically included in electrolytes.

[0085] As the electrolyte, a known solid electrolyte may be used.

[0086] The secondary battery according to an embodiment of the present invention may be a stack type, a winding type, a stack-and-folding type, or a cable type. The secondary battery may be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- or large-sized battery module including a number of battery cells. Preferred examples of the medium- or large-sized device include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, and may be particularly useful in hybrid electric vehicles and renewable energy storage batteries in areas where high output is required.

[0087] Regarding the configuration and manufacturing method of the secondary battery of the present invention, the portions not described above may be configured and manufactured by any method known in the art without any limitations.

[0088] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified in several different forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having ordinary skill in the art.

[0089] Example 1: Preparation of the positive electrode 96g of LFP powder (product name DY-3, Dynanonic) which is a positive electrode active material particle with an average particle size of 1.08μm, 2g of Li250 (Denka) as a conductive material, 1g of PTFE as a binder, and 1g of acrylic modified PTFE (product name A3800, Mitsubishi) as a binder were mixed without solvent at 5000 rpm for 1 minute using a Lab Blender (Waring) as a blender (primary mixing). Next, a shear force of 250N was applied to the mixture at a temperature of 50℃ (PBV-0.1L, Irie Shokai) to perform high shear mixing (secondary mixing). Next, the kneaded secondary mixture was pulverized using a grinder (product name ZM200, Retsch) and sieved to produce a powder-like mixture with a particle size of 300μm to 1000μm. The powder mixture was pressed (Two roll mill MR-3, Inoue Co.) to produce a free-standing film. At this time, the temperature of the rolls of the Two roll mill MR-3 was set to 70° C. to produce a sheet. The free-standing film was then placed on one side of an aluminum current collector with a thickness of 15 μm and pressed to produce a positive electrode.

[0090] Comparative Example 1: Production of Positive Electrode The kneaded secondary mixture in Example 1 was pressed (Two roll mill MR-3, Inoue Co.) to produce a free-standing film, without being crushed and sieved to produce a powdered mixture.

[0091] However, the secondary mixture was too hard to obtain a free-standing film, and therefore it was impossible to carry out the subsequent electrode manufacturing process.

[0092] Comparative Example 2: Production of Positive Electrode A positive electrode was prepared in the same manner as in Example 1, except that only "2 g of PTFE" was used as a binder instead of "1 g of PTFE and 1 g of acrylic modified PTFE" in Example 1.

[0093] Comparative Example 3: Production of Positive Electrode A positive electrode was prepared in the same manner as in Example 1, except that the secondary mixing was performed at 100°C.

[0094] Experimental example 1: Morphological observation of free-standing film (dry electrode film) (1) Appearance evaluation of free-standing films The morphology of the free-standing films prepared in Example 1, Comparative Example 2, and Comparative Example 3 was observed with the naked eye, photographed, and shown in FIG.

[0095] As can be seen in FIG. 5, the free-standing film of Example 1 of the present invention was not found to break at the corners, whereas the free-standing films of Comparative Examples 2 and 3 were found to have cracks at some corners.

[0096] (2) Flexibility evaluation of free-standing films The flexibility of the freestanding films prepared in Example 1, Comparative Example 2, and Comparative Example 3 was measured using a mandrel flex evaluation tester (standard test specifications: ISO 1519:2011, ASTM D522, DIN53152) while gradually decreasing the diameter of a cylindrical device in each of the longitudinal and transverse directions, and the diameter at which cracks started was measured. The measurement results are shown in Table 1 below.

[0097] (3) Tensile strength evaluation of free-standing film To measure the tensile strength in the longitudinal and transverse directions of the freestanding films prepared in Example 1, Comparative Example 2, and Comparative Example 3, electrodes with a width of 20 mm, a length of 200 mm, and a thickness of 200 μm were sampled. The tensile strength of the samples was measured at 50 mm / min using a 180 degree peel measurement method using an Instron UTM device. The maximum force applied until no cracks were generated in the film during the measurement was evaluated as the strength of the freestanding film, and the measurement results are shown in Table 1 below.

[0098] [Table 1]

[0099] Example 2 and Comparative Example 4: Production of Lithium Secondary Battery The positive electrodes prepared in Example 1 and Comparative Example 3 were used to prepare batteries in Example 2 and Comparative Example 4, respectively. The specific preparation method is as follows.

[0100] (1) Manufacturing of negative electrodes A negative electrode active material, natural graphite, a carbon black conductive material, and a PVdF binder were mixed in a weight ratio of 85:10:5 in N-methylpyrrolidone solvent to prepare a composition for forming a negative electrode, which was then applied to a copper current collector to prepare a negative electrode.

[0101] (2) Manufacture of lithium secondary batteries An electrode assembly was prepared by interposing a porous polyethylene separator between the positive electrode prepared in Example 1 or Comparative Example 3 and the negative electrode prepared in (1), and the electrode assembly was placed inside a case, and an electrolyte was injected into the case to prepare a lithium secondary battery. At this time, the electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0M in an organic solvent consisting of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (EC / DMC / EMC mixed volume ratio = 3 / 4 / 3). Through this, the lithium secondary batteries of Example 2 and Comparative Example 4 were prepared.

[0102] Experimental Example 2: Capacity Retention Rate Evaluation of Lithium Secondary Batteries The secondary batteries of Example 2 and Comparative Example 4 prepared above were charged and discharged to evaluate the capacity retention rate, which is shown in Table 2 below. The first and second cycles were charged and discharged at 0.1 C, and the third to 49th cycles were charged and discharged at 0.5 C. The 50th cycle was completed in a charged state (with lithium in the negative electrode).

[0103] Charging conditions: CC (constant current) / CV (low voltage) (4.25V / 0.05C current cut-off) Discharge condition: CC (constant current) condition 3.0V

[0104] The capacity retention rates were calculated as follows:

[0105] Capacity retention rate (%) = (49 discharge capacity / 1 discharge capacity) × 100

[0106] [Table 2]

Claims

1. The present invention comprises a dry electrode film including an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a binder that is multidirectionally fibrillated; and a current collector on which the electrode film is laminated; The multidirectionally fibrillated binder comprises polytetrafluoroethylene and acrylic-modified polytetrafluoroethylene.

2. 2. The electrode for a secondary battery according to claim 1, wherein the multi-directionally fibrillated binder comprises polytetrafluoroethylene and the acrylic modified polytetrafluoroethylene in a weight ratio of 1:9 to 9:

1.

3. 2. The electrode for a secondary battery according to claim 1, wherein the acrylic modified polytetrafluoroethylene is a mixture of polytetrafluoroethylene and an acrylic polymer in a weight ratio of 7:3 to 3:

7.

4. 2. The electrode for a secondary battery according to claim 1, wherein the active material has an average particle size of 0.05 to 2 [mu]m.

5. (a) mixing an active material having an average particle size of 0.05 μm to 3 μm, a conductive material, and a fibrillizable binder; (b) performing shear mixing on the mixture to fiberize the fibrillizable binder to prepare a dry electrode paste; (c) pulverizing the dry electrode mix to produce a powder; (d) compressing the powder into a free-standing film form; and (e) laminating the free-standing film onto a current collector; the fibrillizable binder comprises polytetrafluoroethylene and acrylic modified polytetrafluoroethylene; Step (b) is carried out at a temperature equal to or higher than the glass transition temperature of polytetrafluoroethylene and lower than the glass transition temperature of the acrylic-modified polytetrafluoroethylene; 4. The method for manufacturing an electrode for a secondary battery, wherein step (d) is performed at a temperature equal to or higher than the glass transition temperature of the acrylic-modified polytetrafluoroethylene.

6. 6. The method of claim 5, wherein the powder in step (c) has a particle size of 100 to 1000 [mu]m.

7. 6. The method of claim 5, wherein the fibrillizable binder contains polytetrafluoroethylene and the acrylic modified polytetrafluoroethylene in a weight ratio of 1:9 to 9:

1.

8. 6. The method of claim 5, wherein the acrylic modified polytetrafluoroethylene is a mixture of polytetrafluoroethylene and an acrylic polymer in a weight ratio of 7:3 to 3:

7.

9. A secondary battery comprising the electrode for a secondary battery according to claim 1.

Citation Information

Patent Citations

  • Water-soluble binding composition for secondary battery, mixture for secondary battery electrode, electrode for secondary battery, and lithium ion secondary battery

    JP2014222604A

  • Cathode for lithium-containing batteries and method for producing the same without solvents

    JP2015508220A

  • Dry particle based electro-chemical device and methodsof making same

    KR1020060025230A